The Relationship between Academic Procrastination and Stress Level of Medical Students - Anggoro, Agam (Scientia Psychiatrica, 2023)
The schedule of a medical major is considered to be tight. This can lead to the emergence of greater stress levels in medical students. In the process, there is an act of delaying a job referred to as procrastination is the postponement of an action or task for another time, or even indefinitely. Procrastination of academic tasks can be referred to as academic procrastination. As a result, academic procrastination has become a well-known problem that affects students' performance as measured by grade point average (GPA). This paper will discuss the relationship between medical students' academic procrastination and stress levels.